An antimicrobial peptide screened from casein hydrolyzate by Saccharomyces cerevisiae cell membrane affinity method. (April 2015) - Tang, Wenting; Yuan, Huaning; Zhang, Hui; Wang, Li; Qian, Haifeng; Qi, Xiguang
Abstract: A Saccharomyces cerevisiae cell membrane affinity screening method was developed to separate targeted antimicrobial peptides from the pepsin hydrolyzate of bovine casein. S. cerevisiae cell membranes were first immobilized on the surface of the silica gel to construct an affinity binding medium. A membrane-binding fraction was successfully screened by comparing the RP-HPLC fingerprint chromatograms of the hydrolyzate before and after adsorption with the adsorption medium. The amino acid sequence of the peptide was identified as LRLKKYKVPQL with the use of a matrix-assisted laser desorption/ionisation quadrupole time-of-flight tandem mass spectrometer. The sequence corresponded to amino acid residues 99–109 of bovine αS1 -casein. The results indicated that it is feasible to target screen antimicrobial peptides from protein hydrolyzate using S. cerevisiae cell membranes. The influences of thermal treatment, pH, ions, and enzymes on the activity of the purified peptide were also determined. The activity of the peptide was relatively thermally stable and was pH dependent. It retained more than 90% of its activity in the presence of 15% Na +, K + and pepsin. Trypsin, proteinase K, divalent cation Mg 2+ and Ca 2+ reduced the activity to different extents. The peptide also showed antibacterial effectiveness in fresh pear juice. These observations provide further information on the application of protein-derived antimicrobial peptides in food systems. Highlights: The pepsin hydrolyzate of bovine casein (BCPH) possessed antibacterial activity. Saccharomyces cerevisiae cell membranes (SCM) were immobilized on the surface of the silica. An antimicrobial peptide was separated from BCPH by SCM-binding coupled with RP-HPLC. The activity of the peptide was relatively thermally stable and was pH dependent. The peptide showed antibacterial effectiveness in fresh pear juice.